The reasonable term of preventive detention in the jurisprudence of The Inter-American Court of Human Rights and in the jurisprudence of Colombia - Martínez Espinosa, Luisa Fernanda (2022)
This article addresses the importance of the Jurisprudence of the Inter-American Court of Human Rights, its interpretative and binding nature within the internal normative systems of each country that have signed international treaties and agreements, as in the Colombian case; The development of the Reasonable Term criterion as a substantial and procedural guarantee is part of the protection of the Human Rights of persons deprived in a preventive way of liberty, this guarantee must be incorporated into internal legislation and applied in a mandatory manner by judicial bodies. It is concluded that the Colombian State, despite never having been convicted of any case in which the excessive duration of preventive detention as a precautionary measure is demonstrated, does exist legal antecedents where it is evidenced that its use in some cases has exceeded the reasonable period that limits the duration of the measure; taking into account the judgments of the Court against other countries regarding this motive as a cause of violation of human rights and on the periodic evaluations regarding the use of preventive detention in the Americas.